2011
DOI: 10.1007/s12011-011-9012-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Trace Element Changes on Dehydroepiandrosterone Sulfate in Healthy and Diabetic States among Middle-Age and Elderly Egyptians

Abstract: The aim of this study was to confirm if there is a link between the alteration in blood levels of trace elements (chromium, copper, lead, cadmium, and zinc) and dehydroepiandrosterone sulfate (DHEAS) in healthy and diabetic states. This study is the first study to test these parameters in Egyptians. The study included 150 subjects divided into the following four groups: healthy middle-aged, healthy elderly, middle-aged diabetics, and elderly diabetics. Our results revealed a statistically significant decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…El Husseiny et al (2011) did not observe relationships between examined by them trace elements (Pb, Cd, Zn, Cu, Cr) and the concentration of DHEAS among middle-aged and elderly Egyptians. They showed that age was a major factor in the decrease in DHEAS.…”
Section: Metalsmentioning
confidence: 65%
“…El Husseiny et al (2011) did not observe relationships between examined by them trace elements (Pb, Cd, Zn, Cu, Cr) and the concentration of DHEAS among middle-aged and elderly Egyptians. They showed that age was a major factor in the decrease in DHEAS.…”
Section: Metalsmentioning
confidence: 65%
“…Thirty full-text articles were reviewed for further assessment. Five articles were excluded because they were duplicate publications [ 14 , 15 , 22 , 24 , 28 ]; another five were excluded because Cd content was measured [ 33 37 ], three studies were excluded because the outcome was gestational diabetes mellitus [ 17 , 18 , 25 ], three were reviews [ 38 40 ], two were excluded because outcomes were related to chronic kidney disease [ 41 ] or renal glomerular damage [ 42 ] and one was excluded because the exposure was Cd in the toenail [ 13 ]. Finally, eleven studies met meta-analysis criteria and were included (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hwalla et al in 2017 and others revealed the absorption of Zinc is lower and compromised in the elderly especially those aged above 60 (Gunasekara et al, 2011) Zn supplementation is necessary as a nutrient for a good quality of life in the elderly (Haase and Rink, 2009; Ijaz et al, 2020; Intorre et al, 2008). El Husseiny et al (2011) observed a significant effect of zinc supplementation on diabetic patients in older age groups. Participants of age ≤50 showed stable plasma zinc (70 ± 32 µg/100 mL), and above this age, the levels were reduced (Jeppsson et al, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…Blood sample was taken from the participants with an empty stomach. Blood was collected using EDTA (ATLAS-Labovac) tube for HbA1c (El Husseiny et al, 2011) and serum zinc blood in a gel tube (Ervin and Kennedy-Stephenson, 2002). A structured questionnaire was used to conduct the demographic data which included age, gender, family history of diabetes, any complication regarding diabetes, pregnancy or lactating female, CVDs and supplementation.…”
Section: Methodsmentioning
confidence: 99%